Root canal overfilling as an influencing factor for the success of endodontic treatment - Ardo Sabir (Dental Journal (Majalah Kedokteran Gigi), 2005)
The goal of endodontic treatment is to keep the teeth as long as possible in the mouth. The obturation process in the root canal is one of the most important processes in endodontic treatment. The purpose of this article is to explain that overfilling is an influencing factor to the success of endodontic treatment. It has been widely known that overfilling should be avoided during an obturation process. Overfilling of the root canal is indicated only in cases which will be followed by apicoectomy, when the foreign material is removed. Accidental overfilling may occur with soft material (for example, certain pastes and cements) or with solid material (such as gutta-percha or silver cones). Such overfilling may cause an unnecessary mechanical and chemical irritation, which hinders the repair of periapical tissue, and thus, diminishes the probability of a successful endodontic treatment prognosis. Many things could cause overfilling, which makes overfilling unpleasant feeling for the patient such as severe pain, periapical lesion, gingival discoloration, periodontal ligament breakage, or even paresthesia. There are several ways to overcome this root canal overfilling, from the conventional endodontic treatment up to endodontic surgery. The main conclusion from this article is to avoid overfilling and the importance of clinicians’ compliance to the right procedures.